2015
DOI: 10.1371/journal.pone.0128276
|View full text |Cite
|
Sign up to set email alerts
|

The Colonisation of Exotic Species Does Not Have to Trigger Faunal Homogenisation: Lessons from the Assembly Patterns of Arthropods on Oceanic Islands

Abstract: Human-caused disturbances can lead to the extinction of indigenous (endemic and native) species, while facilitating and increasing the colonisation of exotic species; this increase can, in turn, promote the similarity of species compositions between sites if human-disturbed sites are consistently invaded by a regionally species-poor pool of exotic species. In this study, we analysed the extent to which epigean arthropod assemblages of four islands of the Azorean archipelago are characterised by nestedness acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 67 publications
1
16
0
Order By: Relevance
“…For instance, Arévalo et al (2010) found that taxonomic homogenization due to alien plants increases with human disturbance in roadside communities, while Connor et al () observed that human colonization did not homogenize Azorean flora in highland ecosystems. Also, in the Azores, colonization of alien species did not trigger homogenization of arthropod assemblages in human‐disturbed landscapes, since alien species revealed to be habitat specialists (Florencio et al ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Arévalo et al (2010) found that taxonomic homogenization due to alien plants increases with human disturbance in roadside communities, while Connor et al () observed that human colonization did not homogenize Azorean flora in highland ecosystems. Also, in the Azores, colonization of alien species did not trigger homogenization of arthropod assemblages in human‐disturbed landscapes, since alien species revealed to be habitat specialists (Florencio et al ).…”
Section: Discussionmentioning
confidence: 99%
“…decrease in biota similarity: heterogenization) can be detected depending on the spatial scale of inquiry. These patterns are affected by both the spatial resolution (Olden et al , Castro et al , Spear and Chown ) and the geographic extent of the study area (McKinney , Cassey et al , Shaw et al ) and also by the taxon (Olden et al , Shaw et al , Florencio et al ), the hemisphere (Castro and Jaksic ) or even the ecosystem (Dar and Reshi ).…”
Section: Introductionmentioning
confidence: 99%
“…For this study, we selected five distinct habitat types covering a large percentage of the total island area with, from the least to the most disturbed, natural forests (NatFor), naturalised vegetation areas (NatVeg), exotic forests (ExoFor), semi‐natural pastures (SemiPast) and intensively managed pastures (IntPast) (Cardoso et al ., ). Compared with previous ecological studies undertaken in the Azores (Borges et al ., ; Cardoso et al ., , ; Florencio et al ., , ), we added naturalised vegetation areas, dominated by Erica azorica , Pittosporum undulatum and Rubus hochstetterorum , as an important habitat for flower‐visiting insects, because of its recent growing extent due to pasture abandonment and combination of native and exotic flora. Detailed features regarding each habitat type are outlined in Table S1.…”
Section: Methodsmentioning
confidence: 99%
“…The process of biotic homogenization has been shown to be dependent on land uses and human disturbance (Florencio et al, 2013; Florencio et al, 2015; Solar et al, 2015). Here we found that human disturbance did not influence ant community similarity.…”
Section: Discussionmentioning
confidence: 99%
“…In Europe, the close proximity of PAs to farmlands and cities means that many of the species contributing to overall biodiversity originate from lands outside the PAs (MEA, 2005). Biotic homogenization may also be generated by environmental changes, such as changes in land use, which promote the geographic expansion of some species and result in the shrinking distributions of others (Florencio et al, 2013; Florencio et al, 2015; Harrison et al, 2014; Solar et al, 2015). However, there is little information available regarding the changes in compositional similarity among local communities that have taken place within PA networks, especially for animals.…”
Section: Introductionmentioning
confidence: 99%